ANALISIS HUBUNGAN SEBARAN TOTAL SUSPENDED SOLID (TSS), SUHU PERMUKAAN LAUT DAN SALINITAS MENGGUNAKAN CITRA LANDSAT-8 STUDI KASUS WILAYAH PESISIR PANTAI KETINGAN SIDOARJO - Indra Putra O.A; Hendrata Wibisana; Siti Zainab (LPPM Universitas Abdurrab, 2024)
Ketingan Beach is no stranger to the people of Sidoarjo, apart from being a beach tourist attraction in the District. Sidoarjo, with its mangrove forest ecosystem as a mangrove tourist attraction, also has historical value, making it a pilgrimage tourist spot. The large number of activities that occur around the Ketingan area can affect the water quality of Ketingan beach itself, if the water quality is poor it can damage the potential of Ketingan beach. Based on this background, it is necessary to carry out water quality measurement research to monitor the distribution of Total Suspended Solid (TSS), Sea Surface Temperature and Salinity in 2023 at Ketingan Beach using Landsat 8 Satellite Imagery. The results of the analysis show that the in situ data value for Total Suspended Solid is 61 ( mg/l) - 152 (mg/l) and for the in situ sea surface temperature of Ketingan Sidoarjo Waters it ranges between 18.4°C - 24.4°C while for in situ salinity it ranges between 31 (ppt) - 34 (ppt). From the image data with the highest correlation value, the Total Suspended Solid value was obtained at 99.60 (mg/l) – 110.82 (mg/l) and for sea surface temperature it ranged between 19.41°C – 24°C while for salinity it ranged between 32 .36 (ppt) - 34.57 (ppt). Meanwhile, the correlation value between Total Suspended Solid (TSS) and Sea Surface Temperature was produced using a correlation test with a value of -0.999974332, which means that these two variables have a very strong negative correlation value. The correlation value between Total Suspended Solid (TSS) and Salinity produces a correlation value of 0.341614101, which means that these two variables have a fairly low positive correlation value. Therefore, this research can be a reference in subsequent research and map the distribution of Total Suspended Solid (TSS), Sea Surface Temperature and Salinity and monitor the increase or decrease in Total Suspended Solid (TSS), Sea Surface Temperature and Salinity. So that it can provide the right solution in making decisions regarding environmental impacts, while in the field of Civil Engineering in the planning and construction sector of water structures such as ports and docks, this research can also be used as a database.